2022
DOI: 10.1002/btpr.3318
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time online monitoring of insect cell proliferation and baculovirus infection using digital differential holographic microscopy and machine learning

Abstract: Real-time, detailed online information on cell cultures is essential for understanding modern biopharmaceutical production processes. The determination of key parameters, such as cell density and viability, is usually based on the offline sampling of bioreactors. Gathering offline samples is invasive, has a low time resolution, and risks altering or contaminating the production process. In contrast, measuring process parameters online provides more safety for the process, has a high time resolution, and thus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…It becomes evident that the values measured offline correspond well with the values measured online over the entire cultivation period. Altenburg et al [ 144 ] showed similar accuracies between the VCD determination using iLineF and offline determination in cultivations with insect cells. The cell aggregation rate correlates with the VCD.…”
Section: Resultsmentioning
confidence: 89%
“…It becomes evident that the values measured offline correspond well with the values measured online over the entire cultivation period. Altenburg et al [ 144 ] showed similar accuracies between the VCD determination using iLineF and offline determination in cultivations with insect cells. The cell aggregation rate correlates with the VCD.…”
Section: Resultsmentioning
confidence: 89%
“…Cell proliferation could be monitored through ML based algorithms. An ML model was trained for monitoring insect cell proliferation and viability percentage upon baculovirus infection in the bioreactor ( Altenburg et al., 2023 ).…”
Section: Ai-based ML Algorithms In Recombinant Protein Productionmentioning
confidence: 99%
“…To assess the impact of timing on low MOI processes, several low MOI bioreactor infections with temperature shifts at different times post-infection were performed. In previous experiments with low MOI (0.01 TCID50/cell), complete baculovirus infection of all insect cells was observed around 40 hpi (Altenburg et al, 2022). Therefore, the temperature shift was conducted between 33-40 hpi.…”
Section: Scale-up To Bioreactors With High Moi Infectionmentioning
confidence: 99%